Retrospective study of mortality in Asiatic lions (Panthera leo persica) in the European breeding population between 2000 and 2014. Issue 1 (January 2017) - Metz, Olivia; Williams, Jonathan; Nielsen, Rikke Kruse; Masters, Nic
Abstract : Although the European population of Asiatic lions ( Panthera leo persica ) has been managed under the European Endangered Species Program (EEP) since 1990, little is known about the health status of the population. This study was designed to characterize mortality for this population through examination of the studbook and other records on 392 Asiatic lions living in the EEP between 2000 and 2014. A total of 270 animals died during the period with 80% of them being under 1 year old. The mortality rate for under 1 year olds was 54%, while the odds of survival of cubs within a litter increased if the dam had had litters previously. Survival to reproductive age was 44%. Post‐mortem reports were requested and the cause of death was obtained for 133 animals. Trauma inflicted by a conspecific and lack of care were common causes of death (26% and 22%, respectively) and were also responsible for most of the neonatal mortalities. Congenital defects were responsible for 9% of deaths, although the true prevalence is likely underestimated. A common necropsy protocol for all Asiatic lion collections is needed to facilitate future studies. Zoo Biol. 36:66–73, 2017. © 2017 Wiley Periodicals, Inc.